Vertical profiles of black carbon and nanoparticles pollutants measured by a tethered balloon in Longyearbyen (Svalbard islands). (1st December 2022) - Cappelletti, David; Petroselli, Chiara; Mateos, David; Herreras, Marcos; Ferrero, Luca; Losi, Niccolò; Gregorič, Asta; Frangipani, Claudia; La Porta, Gianandrea; Lonardi, Michael; Chernov, D.G.; Dekhtyareva, Alena
Abstract: Airborne meteorological and aerosol measurements have been performed in Longyearbyen (Svalbard islands) in the summer of 2018, coupling an instrumental aerosol payload with a meteorological radiosonde deployed on a tethered balloon. More than 70 vertical profiles of aerosol and meteorological properties have been recorded up to a maximum altitude of 1.2 km. As a main result, the present work provides a homogeneous gridded dataset of vertical profiles of equivalent black carbon ( eBC ) and nanoparticles ( NP ) concentrations and associated meteorological data (temperature, T, relative humidity, RH, pressure, P) to be employed for future modelling studies of Arctic pollution. Mean values (±SD) of eBC and NP below 500 m were 110 ± 10 ng m −3 and 1400 ± 400 particles cm −3, respectively. Mean values above 500 m were 150 ± 30 ng m −3 and 1000 ± 350 particles cm −3, respectively. Group medians of maximum eBC and NP concentrations in vertical profiles with temperature inversions were significantly higher than for those without inversion. The dataset has been complemented by continuous ground measurements of eBC with an average value of 208 ± 130 ng m −3 (median value 110 ± 70 ng m −3 ) for the entire campaign; the ground-based background (absence of local emission) eBC value was below 100 ng m −3 while maximum values were in the 1000–2000 ng m −3 range. Median eBC concentration measured at ground for 2 h before the tethered balloon launch was higher when temperature inversion was observed. The ground-based measurements, coupled with aerosol optical depth measurements, allowed for a preliminary discussion of two case studies related to high pollutants concentration events. Graphical abstract: Image 1 Highlights: 72 black carbon and nanoparticle aerosols have been measured in summer 2018. Vertical profiles are influenced by local sources and long-range transport. A homogeneous gridded dataset of vertical profiles has been generated. Case studies of aerosol stratification at ground and black carbon from Eurasia are discussed.